Differentially Expressed Proteins in Primary Endothelial Cells Derived From Patients With Acute Myocardial Infarction. Issue 4 (October 2019) - Nukala, Sarath Babu; Regazzoni, Luca; Aldini, Giancarlo; Zodda, Erika; Tura-Ceide, Olga; Mills, Nicholas L.; Cascante, Marta; Carini, Marina; D'Amato, Alfonsina
Abstract : Endothelial dysfunction is one of the primary factors in the onset and progression of atherothrombosis resulting in acute myocardial infarction (AMI). However, the pathological and cellular mechanisms of endothelial dysfunction in AMI have not been systematically studied. Protein expression profiling in combination with a protein network analysis was used by the mass spectrometry-based label-free quantification approach. This identified and quantified 2246 proteins, of which 335 were differentially regulated in coronary arterial endothelial cells from patients with AMI compared with controls. The differentially regulated protein profiles reveal the alteration of (1) metabolism of RNA, (2) platelet activation, signaling, and aggregation, (3) neutrophil degranulation, (4) metabolism of amino acids and derivatives, (5) cellular responses to stress, and (6) response to elevated platelet cytosolic Ca 2+ pathways. Increased production of oxidants and decreased production of antioxidant biomarkers as well as downregulation of proteins with antioxidant properties suggests a role for oxidative stress in mediating endothelial dysfunction during AMI. In conclusion, this is the first quantitative proteomics study to evaluate the cellular mechanisms of endothelial dysfunction in patients with AMI. A better understanding of the endothelial proteome and pathophysiology of AMI may lead to the identification of new drug targets. Abstract : Supplemental Digital Content is available in the text.